DNA extraction, amplification and analysis of the 28S rRNA portion in sediment-buried copepod DNA in the Great Wall Bay and Xihu Lake, Antarctica - Xu, Zhi-Huan; Jiang, Xiao-Dong; Wang, Gui-Zhong; He, Jian-Feng; Cai, Ming-Hong; Wu, Li-Sheng; Jiang, Jie-Lan; Chen, Xue-Lei (Journal of Plankton Research, 2011)
The Antarctic region, characterized by a constant low temperature, is viewed as an ideal place for protecting biomolecules. In this study, five different DNA extraction methods were used to analyze copepod DNA buried in Antarctic marine and lake sediments for potential studies on copepod distribution and composition in the past. After the comprehensive comparison of DNA extraction efficiency, purity of DNA extracts, time spent and cost per extraction, the E.Z.N.A.™ Soil DNA Kit was viewed as the most suitable DNA extraction method for studying sediment-buried copepod DNA in the polar area. Furthermore, the DNA extracts using this method were subjected to DNA cloning and sequencing. A homology tree based on a ∼300-bp fragment of partial 28S rRNA was established, and two distinct groups were observed: the species Boeckella poppei dominated the lake group, but the marine group was more diverse with a similarity rate as low as 75% among some copepod species. The present study provided a suitable DNA extraction method for analyzing sediment-buried copepod DNA in Antarctica and also offered reliable results on the distribution of sediment-buried copepod DNA. The inferred information could be applied to reconstruct copepod communities in the past and assess the evolutionary processes involved.